2017
DOI: 10.1159/000481460
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Uric Acid Levels on Kidney Disease Progression

Abstract: Background: Hyperuricemia is associated with the progression of chronic kidney disease (CKD), but it is not known whether the relationship is causal. We examined the association of hyperuricemia and uric acid lowering therapy (UALT) with progression of CKD in patients with CKD 3 and 4 in the Cleveland Clinic CKD registry. Methods: We included 1,676 patients with CKD stages 3 and 4 from Ohio, who had measured their uric acid (UA) levels a year prior to the recording of the second eGFR <60 mL/min/1.73 m2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
(37 reference statements)
2
19
0
Order By: Relevance
“…Meanwhile, consistent with previous studies [4][5][6][7][8][9][10][11][12], we found that uric acid levels were negatively correlated with eGFR in all subjects. In the regression analysis, various potential confounders were added in sequential order, but the results revealed only a modest reduction effect (the regression coefficient changed from -0.20 to -0.22 after adjusting for a range of confounders), strengthening the notion of a relationship between uric acid and eGFR.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Meanwhile, consistent with previous studies [4][5][6][7][8][9][10][11][12], we found that uric acid levels were negatively correlated with eGFR in all subjects. In the regression analysis, various potential confounders were added in sequential order, but the results revealed only a modest reduction effect (the regression coefficient changed from -0.20 to -0.22 after adjusting for a range of confounders), strengthening the notion of a relationship between uric acid and eGFR.…”
Section: Discussionsupporting
confidence: 93%
“…The association between uric acid and kidney disease has been previously investigated. Numerous studies reported a positive association between the levels of circulating uric acid and the risk of CKD progression [4][5][6][7][8][9][10][11][12], but this was negated in other studies [13][14][15]. Observational studies experience residual problems of poorly measured or unmeasured confounding factors and reverse causality when the disease process has a long latency period.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperuricemia is associated with increased risk of new-onset kidney disease and progression to chronic kidney disease (CKD). 1 3 ) Xanthine oxidase reductase inhibitors (XOR-I) are used for the treatment of hyperuricemia worldwide. Recently, the effectiveness of novel XOR-I, febuxostat and topiroxostat, was reported.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple factors such as hypertension, diabetes, and proteinuria promote onset and progression of CKD to end stage of renal disease (ESRD) [4,5]. Recent human and animal studies have uncovered that hyperuricemia is also an independent risk factor of CKD and is prevalent in patients with this disease [6]. Thus, understanding the mechanism by which uric acid induces pathological changes in the kidney will aid to develop novel therapeutic approaches for alleviating the progression of CKD.…”
Section: Introductionmentioning
confidence: 99%